Transient Sub-cellular Localization and In Vivo Protein-Protein Interaction Study of Multiple Abiotic Stress-Responsive AteIF4A-III and AtALY4 Proteins in Arabidopsis thaliana - Baruah, Indrani; Baruah, Geetanjali; Sahu, Jagajjit; Singha, Dhanawantari L.; Dekaboruah, Hariprasanna; Velmurugan, Natarajan; Chikkaputtaiah, Channakeshavaiah (Plant molecular biology reporter, 2020)
Major abiotic stress factors such as drought, salinity, hypoxia, and extreme temperatures along with rapid global climate change have had a huge negative impact on agricultural productivity. Understanding the abiotic stress-responsive molecular mechanisms and its associated proteins is extremely important to advance our knowledge towards developing multiple abiotic stress tolerance in plants. Firstly, basic understanding at transient level would be a vital foundation to accomplish this goal. Therefore, our present study aimed at understanding the sub-cellular localization of Eukaryotic Initiation Factor 4A-III (AteIF4A-III), a key DEAD-box RNA helicase, and Always Early 4 (AtALY4), an mRNA export factor, and their in vivo protein-protein interaction with major abiotic stress–associated proteins under control and multiple abiotic stress conditions. AteIF4A-III and AtALY4 were localized to the nucleus as evident by transient protoplast assay. AteIF4A-III has shown strong interaction with a negative regulator of multiple abiotic stresses, Stress Response Suppressor 1 (AtSTRS1) in Bi-FC assay. Further, the flow cytometry analysis has shown the strong interaction between them. Interestingly, under multiple abiotic stress treatment, the interacting partners were rapidly re-localized from nucleus to cytoplasm and cytoplasmic space. Similar results were observed when N- and C-terminal fusions of AteIF4A-III and AtALY4 treated under multiple abiotic stresses. Our study reveals that AteIF4A-III, AtALY4, and abiotic stress–associated protein AtSTRS1 are among the key proteins associated with multiple abiotic stress responses in plants.